How Occupational Health and Safety Affects Employee Productivity and Work Quality - Multazam Multazam (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to identify how much influence employee health and safety has on employee performance. Methodology: Sampling in this study used 96 respondents, the data collection technique was through questionnaires distributed to respondents, and the research variables were Health (X1), Safety (X2), Performance (Y). This study used descriptive analysis with a quantitative approach, and to test the level of reliability using Cronbach Alpha and then the data was processed with Multiple Linear Regression Analysis. Hypothesis testing used the F Test and t Test with a significance level of 10%. Researchers used SPSS Version 17. Main Findings: From the results of multiple linear regression analysis shows that employee performance is influenced by health variables and work safety variables. The determination results (R2) use the adjusted r square value, because it uses regression with more than one dependent variable, which is 0.685, which means that health variables and work safety variables are able to explain employee performance by 69% while the remaining 31% is influenced by other variables not studied. From the results of the F test and t test calculations, it can be seen that health variables and work safety variables together affect employee performance and the most dominant variable is the work safety variable. Novelty/Originality of this study: This study presents a new perspective by evaluating the effectiveness of employee participation-based K3 implementation as a mediating variable that has not been widely researched in relation to increasing individual productivity and performance in industrial sector organizations.